Studying large organizations and elites: limits and challenges of fieldwork - Barroso, M. (2018)
In this article, we analyse some of the methodological challenges that social scientists face when studying large organisations and elites. Based in our own experience using qualitative research methods in this field of study, we propose a reflexion on the most common obstacles and limitations regarding fieldwork, data collection, interviewing and data analysis. Apart from presenting the particularities of large organisations and elites as research objects, and to discuss concrete strategies to access the field and to collect data, we reflect on qualitative interviews as complex processes of interaction, exploring gender and power relations as central dimensions when undertaking research. With this article we intent to stimulate debate on the pivotal role of the researcher in the research process and on the importance of adopting a reflexive perspective in all stages of research.